2022
DOI: 10.1111/jocd.15359
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of anti‐aging effects of combined therapy—Azelaic acid, phytic acid, and vitamin C applied layer by layer in females with Fitzpatrick skin types II and III

Abstract: Introduction Vitamins C, E, and A and substances of plant origin, including azelaic acid and phytic acid are frequently used in cosmetic preparations to counteract oxidative stress and negative effects of free radicals. The aim of the study was to evaluate a novel combined therapy consisting of azelaic acid, ascorbic acid, and phytic acid applied layer on layer. Methods Twenty study participants received a series of eight treatments performed every 7 days. Twenty percent azelaic acid and then 30% phytic acid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…No studies on azelaic acid and skin aging met the inclusion criteria. While there are a handful of published studies investigating the use of azelaic acid in conjunction with other ingredients, for example, a 2022 study wherein three active compounds resulted in a significant improvement in erythema and hyperpigmentation, 57 none are RCTs and no studies have been conducted on the use of azelaic acid as a monotherapy in skin aging.…”
Section: Resultsmentioning
confidence: 99%
“…No studies on azelaic acid and skin aging met the inclusion criteria. While there are a handful of published studies investigating the use of azelaic acid in conjunction with other ingredients, for example, a 2022 study wherein three active compounds resulted in a significant improvement in erythema and hyperpigmentation, 57 none are RCTs and no studies have been conducted on the use of azelaic acid as a monotherapy in skin aging.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, azelaic acid and chlorogenic acid are also reported to harbor antioxidant effects which are widely topically used in acne and other inflammatory skin diseases ( Markiewicz-Tomczyk et al, 2022 ; Szabo et al, 2022 ). In our study, azelaic acid was relatively increased in the DKD-FG group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that vitamin C is capable of repairing DNA, alleviating oxidative stress, and modulating the activity of telomeres in the aging process, thereby eventually leading to longevity [221]. Vitamin C was generally used as a supplement in cosmetic and dermatologic products for anti-skin-aging purposes [208,[222][223][224]. For instance, a split-face, randomized controlled trial indicated that vitamins C and E improved skin color, elasticity, radiance, smoothness, scaliness, and wrinkles of fifty female volunteers aged 30-65 years [225].…”
Section: Water-soluble Vitaminsmentioning
confidence: 99%